The safety and effectiveness of Santulli enterostomy in neonatal intestinal conditions - Yue, Ming; Yang, Heying; Cui, Mingxia; Yuan, Yuhang; Zhang, Ning; Zhang, Xiangyu; Li, Yan (Frontiers in Pediatrics, 2023)
Background: As an end stoma, Santulli enterostomy provides early restoration of intestinal continuity without formal laparotomy. Short amputation of the common limb enables closure on a side to restore anatomic continuity without sacrificing valuable intestine; additionally, the procedure is simple and safe. Most newborns who require enterostomy might benefit from Santulli enterostomy; however, several pediatric surgeons lack information regarding this procedure. Therefore, we have reviewed our experience about Santulli enterostomy and explore the advantages and indications in neonatal intestinal conditions. Methods: The clinical data of 76 neonates who underwent enterostomy were obtained. The patients were divided into two groups: the Santulli group with 33 cases who underwent Santulli enterostomy, and the control group with 43 cases who underwent double- or single-lumen ostomy. The general data of the two groups were analyzed, and the perioperative/postoperative complications, clinical data and the long-term outcomes were compared. Results: There was no difference in the demographic informations, the level of enterostomy, the rate of high-sight stoma, the operative time and bleeding of enterostomy between the two groups. Compared to the control group, the operative time of ostomy closure was less in the Santulli group (53.00 vs. 152.47, P<0.001). The duration of parenteral nutrition (27.45 vs. 44.56, P=0.010), the mean interval of initial enterostomy to stomal closure (131.21 vs. 216.42, P<0.001), and length of stay (46.00 vs. 67.60, P=0.007) were shorter, while the incidence of postoperative complications and hospitalization costs (11.21 vs. 15.49, P=0.006) were lower. The Santulli procedure can reduce the morbidity of high output ostomy (2 vs. 10, P=0.042) and short bowel syndrome (3 vs. 132, P=0.025), shorten the discrepancy of diameter between the proximal and distal segments, maximize the available intestine, and monitor the movement of the distal bowel. The length of incision was shorter, and the catch-up growth was significantly faster in the santulli group. Conclusions: Santulli enterostomy is a superior procedure in the treatment of neonatal intestinal conditions, in terms of fewer complications,faster catch-up growth, shorter hospitalization time and treatment duration. It should be the procedure of choice in several newborns with intestinal conditions that require ostomy.